Preparation method and application of montmorillonite / chitosan aluminum ion imprinting material

The preparation of montmorillonite/chitosan aluminium ion imprinting materials through the composite material of montmorillonite and chitosan has solved the problems of low aluminum ion removal efficiency and insufficient material stability in the prior art, and achieved high efficiency under acidic conditions Aluminum ion removal and multiple recycling of materials.

CN119176972APending Publication Date: 2024-12-24JIANGXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411036492.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove aluminum ions, especially under acidic conditions, and its adsorbent is easily soluble in water, which limits its application range and regeneration.

Method used

Montmorillonite and chitosan composite material were used to prepare montmorillonite/chitosan ionic blotting material by thermally activating the combination of montmorillonite, acid modification and chitosan, and remove it with its high selectivity and stability. Aluminum ions.

Benefits of technology

It realizes high-efficiency aluminum ion removal under acidic conditions, improves the mechanical strength and acid resistance of the material, and maintains high removal rate and selectivity after multiple cycles, has low material loss rate, good chemical stability and Environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176972A_ABST
    Figure CN119176972A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a montmorillonite / chitosan aluminum ion imprinting material, and relates to the technical field of mineral materials and environmental protection. The specific preparation process comprises the following steps: by taking montmorillonite as a raw material, preferentially releasing octahedral aluminum ions in the montmorillonite through thermal activation and acid activation to form a three-dimensional hole structure corresponding to Al < 3 + > to synthesize the montmorillonite aluminum ion imprinted material; uniformly mixing the montmorillonite aluminum ion imprinting material, chitosan and aluminum sulfate in a deionized water solution; heating in a reaction kettle, and carrying out heat preservation reaction; and eluting the aluminum ions with sodium hydroxide to obtain the montmorillonite / chitosan aluminum ion imprinting material. According to the preparation method and application of the montmorillonite / chitosan aluminum ion imprinting material, the composite aluminum ion imprinting material with strong selectivity on aluminum ions is synthesized by taking chitosan as a functional monomer and montmorillonite as a carrier, the synthesis process and process are simple, a cross-linking agent does not need to be added, and stable adsorption can be realized under an acidic condition; and the chitosan and the montmorillonite are simple in source and relatively low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mineral materials and environmental protection, in particular to a preparation method and application of a montmorillonite / chitosan aluminum ion imprinted material. Background Art

[0002] Aluminum (Al) is one of the most abundant metal elements in the earth's crust and is widely present in nature. However, with the acceleration of industrialization, human activities have caused a large amount of aluminum compounds to enter water, soil and atmosphere, causing a series of environmental and health problems. 3+ ) As one of the main forms of aluminum, it has potential harm to the ecological environment and human health. Therefore, the removal of aluminum ions has become one of the important issues to be solved in the field of water treatment and environmental protection.

[0003] Ion imprinting technology is a new type of molecular recognition technology that aims to prepare materials with high selective adsorption capacity for specific ions. This technology achieves selective adsorption of target ions by introducing template ions into the polymer matrix and forming imprinting sites that match the shape and size of the template ions during the polymerization process. Ion imprinted materials have high selectivity, high adsorption capacity and good regeneration ability. Due to the high match between the imprinting sites and the target ions in shape and size, ion imprinted materials have extremely high selectivity for the target ions. In addition, the preparation method of ion imprinted materials is flexible, and different functional monomers and polymerization methods can be selected according to different application requirements.

[0004] Chitosan molecules contain a large number of amino and hydroxyl groups, which can form complexes with a variety of metal ions. Therefore, chitosan is often used as a functional monomer to prepare ion-imprinted materials. Chitosan aluminum ion imprinted materials have the following advantages: Since the imprinted sites are highly matched with the shape and size of aluminum ions, chitosan ion imprinted materials have extremely high selectivity for aluminum ions. The amino and hydroxyl groups in chitosan molecules can provide a large number of coordination sites, making chitosan aluminum ion imprinted materials have a higher aluminum ion adsorption capacity. For example, n-Methacryloyl-l-glutamic acid (MAGA) was used as the functional monomer. First, aluminum ions were complexed with MAGA, and then aluminum ion imprinted poly(hydroxyethyl methacrylate)-n-methacryloyl-l-glutamic acid (MIP) microspheres were prepared by suspension polymerization. Subsequently, 0.1 mol / L EDTA solution was used to remove the template ions (i.e., Al 3+ The specific surface area of ​​MIP microspheres is 55.6 m 2 / g, particle size range is 63~140μm, expansion rate is 102%. Element analysis results show that the MAGA content of MIP microspheres is 640μmol / g, 3+The maximum adsorption capacity of MIP microspheres is 122.9 μmol / g. 3+ / Ni 2+ 、Al 3+ / Cu 2+ and Al 3+ / Fe 3+ The relative selectivity coefficients of chitosan are 1427, 14.8 and 6.2 times that of non-imprinted matrices, respectively. However, since chitosan is a linear polymer, under acidic conditions, the amino groups in its molecules are protonated and easily soluble in water, resulting in the loss of the adsorbent, limiting its application range and being unfavorable for separation and utilization.

[0005] The crystal structure of montmorillonite is a 2:1 layered structure, that is, an octahedral layer is sandwiched between two tetrahedral layers. The interlayers of montmorillonite have a large specific surface area and adjustable interlayer spacing, which gives it good ion exchange and adsorption properties. In addition, the surface of montmorillonite is rich in silicon-oxygen tetrahedrons and aluminum-oxygen octahedra. These structural units can form complexes with a variety of metal ions and organic molecules to enhance their adsorption capacity. The preparation of montmorillonite adsorbent materials generally includes steps such as modification and compounding of montmorillonite. The specific surface area and adsorption properties of montmorillonite can be improved by acid modification, alkali modification or organic modification of montmorillonite. In addition, by compounding montmorillonite with other functional materials (such as chitosan and graphene), multifunctional adsorbent materials can be prepared to further enhance their adsorption properties and application range. For example, Hailin Wang et al. used Co 2+ Chitosan / modified montmorillonite was used as template ion to remove heavy metal cations. The mass ratio of chitosan to montmorillonite has a great influence on the adsorption performance of the composite material. Compared with chitosan alone or modified montmorillonite alone, the chitosan and modified montmorillonite composite material has a better adsorption performance on Co 2+ The adsorption effect of the composite material was significantly enhanced, depending on the specific experimental conditions and the molecular weight of chitosan. When the mass ratio of chitosan to montmorillonite was 0.25, the maximum adsorption value of the composite material was 150 mg / g, which was much higher than the adsorption values ​​reported in other studies.

[0006] Montmorillonite / chitosan aluminum ion imprinted material is a new type of composite adsorbent material prepared by combining the high selectivity of chitosan with the high adsorption capacity of montmorillonite. It is of great significance to achieve stable and efficient removal of aluminum ions by utilizing the specific recognition ability of chitosan aluminum ion imprinted material for aluminum ions and the ion exchange capacity and stability of montmorillonite aluminum ion imprinted material. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a method for preparing a montmorillonite / chitosan aluminum ion imprinted material and its application, which solves the problems mentioned in the above background technology.

[0008] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a montmorillonite / chitosan aluminum ion imprinted material, comprising the following steps:

[0009] S1. Put montmorillonite into a muffle furnace, heat it up and keep it warm for a period of time, and then cool it to room temperature to obtain heat-activated montmorillonite; then put the heat-activated montmorillonite into a conical flask, add the acid solution, stir it under constant temperature, filter the mixed solution, wash the montmorillonite aluminum ion imprinted material with ethanol and deionized water alternately until the pH is 7, and then dry it in a vacuum drying oven;

[0010] S2, mixing chitosan, montmorillonite aluminum ion imprinted material and aluminum sulfate in a deionized water solution, pouring into a reactor and heating, cooling to room temperature, filtering the sample, and grinding with ethanol to obtain a montmorillonite / chitosan aluminum ion polymer material;

[0011] S3, soaking the montmorillonite / chitosan aluminum ion polymer material in a sodium hydroxide solution to remove aluminum ions in the montmorillonite / chitosan aluminum ion polymer material;

[0012] S4. Wash the sample alternately with ethanol and deionized water until the pH value is 7, and then place it in a vacuum drying oven for drying to obtain montmorillonite / chitosan aluminum ion imprinted material.

[0013] Preferably, in step S1, the purity of montmorillonite is 80% to 99%, the temperature is raised to 400 to 700°C, and the insulation time is 15 min to 3 h; the acid solution is any one of sulfuric acid solution, nitric acid solution, hydrochloric acid solution, and phosphoric acid solution, with a concentration of 1 to 3 mol / L, a constant temperature of 55 to 95°C, a solid-liquid ratio of 1:(20 to 100), and the acid dissolution time is 1 to 5 h.

[0014] Preferably, in step S2, the mass ratio of chitosan to montmorillonite aluminum ion imprinting material is 1:2-3:1, and the mass ratio of chitosan to aluminum sulfate is 1:1-4.0:1.

[0015] Preferably, in step S2, the temperature is heated to 110-150° C. for 6-14 hours.

[0016] Preferably, in step S3, the concentration of the sodium hydroxide solution is 0.05-0.4 mol / L, the volume is 50-250 mL, and the soaking time is 1.5-4 h.

[0017] Preferably, in step S4, the drying temperature is 60 to 90° C., and the drying time is 6 to 12 hours.

[0018] Application of an ion-imprinted material prepared by a method for preparing a montmorillonite / chitosan aluminum ion imprinted material in selectively removing aluminum ions in a solution comprises the following steps:

[0019] The montmorillonite / chitosan aluminum ion imprinted material was added to a mixed solution of aluminum ions and rare earth ions whose pH value was adjusted with sulfuric acid or sodium hydroxide, and placed in a constant temperature oscillation box at 25°C for oscillation, and then filtered and separated to obtain a supernatant. The aluminum ion concentration and rare earth ion concentration in the supernatant were detected by ICP, and the removal rate and selectivity coefficient of the montmorillonite aluminum ion imprinted material for aluminum ions were calculated.

[0020] Preferably, the dosage of the montmorillonite / chitosan aluminum ion imprinting material is 3 g / L to 5 g / L; the pH value of the mixed solution of aluminum ions and rare earth ions is 2 to 4; and the constant temperature oscillation time is 5 min to 3 h.

[0021] Beneficial Effects

[0022] The present invention provides a preparation method and application of montmorillonite / chitosan aluminum ion imprinted material. Compared with the prior art, it has the following beneficial effects:

[0023] (1) The preparation method and application of the montmorillonite / chitosan aluminum ion imprinted material, by using chitosan as a functional monomer and montmorillonite as a carrier, synthesizes a composite aluminum ion imprinted material with strong selectivity for aluminum ions, the synthesis process is simple, no cross-linking agent is required, and the chitosan and montmorillonite are simple in source and low in cost;

[0024] (2) Compared with other methods for preparing chitosan aluminum ion imprinted materials, the preparation method and application of the montmorillonite / chitosan aluminum ion imprinted material have greatly improved mechanical strength and acid resistance, and have the characteristics of appropriate strength and stable adsorption under acidic conditions. Compared with montmorillonite ion imprinted materials, the selectivity is significantly improved;

[0025] (3) The preparation method and application of the montmorillonite / chitosan aluminum ion imprinted material, the montmorillonite / chitosan aluminum ion imprinted material used still has a high removal rate and selectivity for aluminum ions in the solution after multiple cycles of reuse, and the material loss rate is extremely low, and has good chemical stability;

[0026] (4) The preparation method and application of the montmorillonite / chitosan aluminum ion imprinted material have simple process, no need to use a cross-linking agent, low cost, no secondary pollution, green and environmentally friendly, significant environmental and economic benefits, and are suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the synthesis process of the present invention;

[0028] Figure 2 FT-IR images of the chitosan aluminum ion imprinted material, the montmorillonite aluminum ion imprinted material and the montmorillonite / chitosan aluminum ion imprinted material of the present invention;

[0029] Figure 3 The results of the montmorillonite / chitosan aluminum ion imprinting material on Al under different sodium hydroxide concentrations in Example 1 of the present invention are shown in FIG. 3+ Removal rate graph;

[0030] Figure 4 The montmorillonite / chitosan aluminum ion imprinting material under different pH conditions of Example 2 of the present invention is Al 3+ Removal rate graph;

[0031] Figure 5 The different amounts of montmorillonite / chitosan aluminum ion imprinting materials used in Example 3 of the present invention are 3+ Removal rate and desorption rate curve;

[0032] Figure 6 It is a curve diagram of the Al3+ removal rate of the montmorillonite / chitosan aluminum ion imprinting material at different oscillation times in Example 4 of the present invention;

[0033] Figure 7 The results of the montmorillonite / chitosan aluminum ion imprinting material on Al under different regeneration times in Example 6 of the present invention are shown in Table 1. 3+ Removal rate graph. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] When the temperature is not particularly limited in the following embodiments of the present invention, it is all room temperature conditions. Room temperature refers to the natural room temperature conditions in all seasons without additional cooling or heating treatment. Generally, the room temperature is controlled at 10-30°C, preferably 15-25°C.

[0036] The preparation method of the montmorillonite aluminum ion imprinted material is as follows: montmorillonite with a purity of 80% to 99% is placed in a muffle furnace, heated to 400 to 700°C and kept warm for 15 minutes to 3 hours, and cooled to room temperature to obtain heat-activated montmorillonite; then the heat-activated montmorillonite is placed in a conical flask, an acid solution with a concentration of 1 to 3 mol / L (any one of sulfuric acid solution, nitric acid solution, hydrochloric acid solution, and phosphoric acid solution) is added, wherein the solid-liquid ratio is 1:(20 to 100), and then the mixture is placed at a constant temperature of 55 to 95°C and stirred for 1 to 5 hours, the mixed solution is filtered, the montmorillonite aluminum ion imprinted material is alternately washed with ethanol and deionized water until the pH value is 7, and then the mixture is placed in a vacuum drying oven for drying to obtain the montmorillonite aluminum ion imprinted material. Chitosan, montmorillonite aluminum ion imprinted material and aluminum sulfate are uniformly mixed in a deionized water solution, poured into a reactor for heating, cooled to room temperature and filtered to obtain a montmorillonite / chitosan aluminum ion polymer material; ground with ethanol to obtain a chitosan aluminum ion polymer material, and then immersed in a sodium hydroxide solution to remove aluminum ions in the montmorillonite / chitosan aluminum ion polymer material; then the montmorillonite / chitosan aluminum ion polymer material from which aluminum ions are removed is alternately washed with ethanol and deionized water until the pH value is 7, and then placed in a vacuum drying oven for drying to obtain the montmorillonite / chitosan aluminum ion imprinted material.

[0037] Example 1

[0038] A method for preparing a montmorillonite / chitosan aluminum ion imprinted material comprises the following steps: dispersing 22.5 g of montmorillonite aluminum ion imprinted material, 30 g of chitosan and 10 g of aluminum sulfate 18 hydrate into deionized water, stirring with a magnetic force to obtain a uniform mixed solution, transferring the mixed solution into a reaction kettle and heating it to 130° C., vacuum filtering, grinding the mixed solution with ethanol in an agate mortar, and transferring the mixed solution into 0.05 mol / L, 0.1 mol / L, 0.25 mol / L, 0.3 mol / L and 0.4 mol / L sodium hydroxide solutions, respectively, to elute the aluminum ion polymerized with the composite material. The sample was washed alternately with ethanol and deionized water until the pH value was 7, and dried in a vacuum drying oven at 60°C for 6 hours to obtain montmorillonite / chitosan aluminum ion imprinted material; 0.1 g of montmorillonite / chitosan aluminum ion imprinted material was added to 50 mL of a 100 mg / L mixed solution of aluminum and lanthanum ions whose pH value was adjusted to 4 with sulfuric acid or sodium hydroxide, and the mixture was shaken in a constant temperature shaking box at 25°C for 2 hours. The supernatant was separated by filtration, and the concentrations of aluminum ions and lanthanum ions in the supernatant were detected by ICP, and the selectivity coefficient of the montmorillonite / chitosan aluminum ion imprinted material for aluminum ions was calculated.

[0039] Depend on Figure 3 It can be seen that the montmorillonite / chitosan aluminum ion imprinted material has a good effect on Al 3+The selectivity coefficient reaches a peak value when the sodium hydroxide concentration is 0.25 mol / L, and the selectivity coefficient reaches 22.2.

[0040] Example 2

[0041] A method for preparing a montmorillonite / chitosan aluminum ion imprinted material comprises the following steps: dispersing 22.5 g of montmorillonite aluminum ion imprinted material, 30 g of chitosan and 10 g of aluminum sulfate 18 hydrate into deionized water, stirring with magnetic force to obtain a uniform mixed solution, transferring the mixed solution into a reaction kettle and heating it to 130° C., vacuum filtering, grinding the mixed solution with ethanol in an agate mortar, transferring the mixed solution into a 0.25 mol / L sodium hydroxide solution to elute aluminum ions polymerized with the composite material, washing the mixed solution with ethanol and deionized water alternately until the pH value is 7, and evaporating the mixed solution at 60° C. The mixture was dried in a vacuum drying oven for 6 hours to obtain montmorillonite / chitosan aluminum ion imprinted material; 0.1 g of montmorillonite / chitosan aluminum ion imprinted material was added to 50 mL of a 100 mg / L mixed solution of aluminum and lanthanum ions whose pH values ​​were adjusted to 2, 2.5, 3, 3.5, and 4 with sulfuric acid or sodium hydroxide, respectively, and the mixture was oscillated in a constant temperature oscillation oven at 25°C for 2 hours. The supernatant was separated by filtration, and the concentrations of aluminum ions and lanthanum ions in the supernatant were detected by ICP, and the selectivity coefficient of the montmorillonite / chitosan aluminum ion imprinted material for aluminum ions was calculated.

[0042] Depend on Figure 4 It can be seen that the montmorillonite / chitosan aluminum ion imprinted material has a good effect on Al 3+ The selectivity coefficient reaches a peak value at pH 4, reaching above 22.2.

[0043] Example 3

[0044] A preparation method of a montmorillonite / chitosan aluminum ion imprinted material comprises the following steps: dispersing 22.5g of montmorillonite aluminum ion imprinted material, 30g of chitosan and 10g of aluminum sulfate 18hydrate into deionized water, stirring with magnetic force to obtain a uniform mixed solution, transferring the mixed solution into a reaction kettle and heating it to 130°C, vacuum filtering, grinding the mixed solution with ethanol in an agate mortar, transferring the mixed solution into a 0.25mol / L sodium hydroxide solution to elute aluminum ions polymerized with the composite material, washing the mixed solution with ethanol and deionized water alternately until the pH value is 7, and drying the mixed solution in a vacuum drying oven at 60°C. The mixture was dried for 6 hours to obtain montmorillonite / chitosan aluminum ion imprinted material; 0.06 g, 0.12 g, 0.20 g, 0.24 g and 0.26 g of montmorillonite / chitosan aluminum ion imprinted material were added into 50 mL of a 100 mg / L mixed solution of aluminum and lanthanum ions whose pH value was adjusted to 4 with sulfuric acid or sodium hydroxide, and the mixture was shaken in a constant temperature shaking box at 25°C for 2 hours. The supernatant was separated by filtration, and the concentrations of aluminum ions and lanthanum ions in the supernatant were detected by ICP, and the selectivity coefficient of montmorillonite / chitosan aluminum ion imprinted material for aluminum ions was calculated.

[0045] Depend on Figure 5 It can be seen that with the increase of the amount of montmorillonite / chitosan aluminum ion imprinted material, the montmorillonite / chitosan aluminum ion imprinted material has a greater 3+ The selectivity coefficient reaches a peak value when the dosage is 0.2 g, and the selectivity coefficient reaches above 418.4.

[0046] Example 4

[0047] A method for preparing a montmorillonite / chitosan aluminum ion imprinted material comprises the following steps: dispersing 22.5 g of montmorillonite aluminum ion imprinted material, 30 g of chitosan and 10 g of aluminum sulfate 18 hydrate into deionized water, stirring with a magnetic force to obtain a uniform mixed solution, transferring the mixed solution into a reaction kettle and heating it to 130° C., vacuum filtering, grinding the mixed solution in an agate mortar with ethanol, transferring the mixed solution into a 0.25 mol / L sodium hydroxide solution to elute aluminum ions polymerized with the composite material, washing the mixed solution with ethanol and deionized water alternately until the pH value is 7, and quenching the mixed solution in a vacuum oven at 60° C. The mixture was dried in a drying oven for 6 hours to obtain montmorillonite / chitosan aluminum ion imprinted material; 0.2 g of montmorillonite / chitosan aluminum ion imprinted material was added to 50 mL of a 100 mg / L mixed solution of aluminum and lanthanum ions whose pH value was adjusted to 4 with sulfuric acid or sodium hydroxide, and the mixture was oscillated in a constant temperature oscillating oven at 25°C for 5 min, 30 min, 1 h, 2 h, and 3 h, respectively, and the supernatant was separated by filtration. The concentrations of aluminum ions and lanthanum ions in the supernatant were detected by ICP, and the selectivity coefficient of the montmorillonite / chitosan aluminum ion imprinted material for aluminum ions was calculated.

[0048] Depend on Figure 6 It can be seen that the montmorillonite / chitosan aluminum ion imprinted material has a good effect on Al 3+ The selectivity coefficient reaches a peak value when the oscillation time is 1 h, and the selectivity coefficient reaches above 418.4.

[0049] Example 5

[0050] A preparation method of a montmorillonite / chitosan aluminum ion imprinted material comprises the following steps: dispersing 22.5g of montmorillonite aluminum ion imprinted material, 30g of chitosan and 10g of aluminum sulfate 18hydrate into deionized water, stirring with magnetic force to obtain a uniform mixed solution, transferring the mixed solution into a reaction kettle and heating it to 130°C, vacuum filtering, grinding the mixed solution in an agate mortar with ethanol, transferring the mixed solution into a sodium hydroxide solution of a certain concentration and eluting aluminum ions polymerized with the composite material, washing the mixed solution with ethanol and deionized water alternately until the pH value is 7, and drying the mixed solution in a vacuum drying oven at 60°C. Dry for 6 hours to obtain montmorillonite / chitosan aluminum ion imprinted material; add 0.2g of montmorillonite / chitosan aluminum ion imprinted material to 50mL of aluminum ion solution adjusted to pH 4 with sulfuric acid or sodium hydroxide and mixed with lanthanum ion, yttrium ion and gadolinium ion, respectively, oscillate in a constant temperature oscillating box at 25°C for 1h, filter and separate to obtain supernatant, use ICP to detect the concentrations of aluminum ion and lanthanum ion, yttrium ion and gadolinium ion in the supernatant, and calculate the selectivity coefficient of montmorillonite / chitosan aluminum ion imprinted material to aluminum in different mixed solutions. Table 1 is a data table of the selectivity coefficient of montmorillonite / chitosan aluminum ion imprinted material to aluminum in mixed solutions of aluminum ion and different rare earth ions in this embodiment.

[0051] Table 1

[0052] type <![CDATA[D Al(Ⅲ) ]]> <![CDATA[D x ]]> α Aluminum / Lanthanum 34.2191 0.08178 418.4294 Aluminum / Yttrium 2.04 0.061 33.62694 Aluminum / Gadolinium 2.12 0.082 25.881

[0053] It can be seen from Table 1 that when aluminum ions are mixed with lanthanum ions, yttrium ions and gadolinium ions respectively, the selectivity coefficients of the montmorillonite / chitosan aluminum ion imprinted material for aluminum are 418.43, 33.63 and 25.89 respectively. The selectivity coefficient of the montmorillonite / chitosan aluminum ion imprinted material mixture reaches the maximum when aluminum and lanthanum ions are mixed.

[0054] Example 6

[0055] A preparation method of a montmorillonite / chitosan aluminum ion imprinted material comprises the following steps: dispersing 22.5g of montmorillonite aluminum ion imprinted material, 30g of chitosan and 10g of aluminum sulfate 18hydrate into deionized water, stirring with magnetic force to obtain a uniform mixed solution, transferring the mixed solution into a reaction kettle and heating it to 130°C, vacuum filtering, grinding the mixed solution in an agate mortar with ethanol, transferring the mixed solution into a sodium hydroxide solution of a certain concentration to elute aluminum ions polymerized with the composite material, washing the sample with ethanol and deionized water alternately until the pH value is 7, and drying the sample in a vacuum drying oven at 60°C for 6 hours to obtain the montmorillonite / chitosan aluminum ion imprinted material; adding 0.2g of the montmorillonite / chitosan aluminum ion imprinted material into 50mL of a molten salt solution heated with sulfuric acid or hydroxide ether; The mixture was added into a 100 mg / L mixed solution of aluminum and lanthanum ions whose pH value was adjusted to 4 by sodium chloride, and oscillated in a constant temperature oscillating box at 25°C for 1 hour. The supernatant was separated by filtration, and the concentrations of aluminum ions and lanthanum ions in the supernatant were detected by ICP, and the selectivity coefficient of the montmorillonite / chitosan aluminum ion imprinted material for aluminum ions was calculated. The solid particles separated by filtration, namely the montmorillonite / chitosan aluminum ion polymer material, were transferred into 200 mL of 2.5 mol / L sulfuric acid solution to elute the aluminum ions polymerized with the montmorillonite / chitosan aluminum ion imprinted material, and the sample was washed alternately with ethanol and deionized water until the pH value was 7, and dried in a vacuum drying oven at 60°C for 6 hours to obtain the regenerated montmorillonite aluminum ion imprinted material, which was reused according to the original process.

[0056] Depend on Figure 7 It can be seen that the selectivity of montmorillonite / chitosan aluminum ion imprinted material continues to decrease with the increase of adsorption-desorption cycles, but the selectivity coefficient in the fifth adsorption-desorption cycle remains at 236.7.

[0057] like Figure 2 As shown, the montmorillonite / chitosan aluminum ion imprinted material has a peak at 465 cm -1 and 523cm -1 The structure of montmorillonite aluminum ion imprinted material is retained at 2918cm, which are Si-O-Si and Al-O-Si bending vibration peaks respectively. The montmorillonite / chitosan aluminum ion imprinted material has a peak at 2918cm compared with the montmorillonite aluminum ion imprinted material. -1 、1382cm -1 、1320cm -1 New absorption peaks appeared at 3628cm, which corresponded to the upper -CH2 vibration peak, CH bending vibration peak, CN stretching vibration peak and NH bending vibration peak of the pyranose ring. This belongs to the structure of chitosan aluminum ion imprinted material, indicating that the chitosan aluminum ion imprinted material was successfully loaded on the montmorillonite aluminum ion imprinted material; the montmorillonite aluminum ion imprinted material has a peak at 3628cm -1 、3434cm -1The characteristic peak of -OH at 3450 cm-1 was shifted to 3450 cm-1 due to the increase in the number of hydroxyl and amine groups caused by the introduction of chitosan aluminum ion imprinting material. -1 .

[0058] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0059] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0060] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a montmorillonite / chitosan aluminum ion imprinted material, characterized in that: The following steps are involved: S1, placing montmorillonite in a muffle furnace, heating and keeping the temperature for a period of time, cooling to room temperature, and obtaining heat-activated montmorillonite; then placing the heat-activated montmorillonite in a conical flask, adding an acid solution, stirring under constant temperature, filtering the mixed solution, washing the montmorillonite aluminum ion imprinted material with ethanol and deionized water alternately until the pH value is 7, and then drying in a vacuum drying oven to obtain the montmorillonite aluminum ion imprinted material; S2, mixing chitosan, montmorillonite aluminum ion imprinted material and aluminum sulfate in a deionized water solution, pouring into a reactor and heating, cooling to room temperature, filtering the sample, and grinding with ethanol to obtain a montmorillonite / chitosan aluminum ion polymer material; S3, soaking the montmorillonite / chitosan aluminum ion polymer material in a sodium hydroxide solution to remove aluminum ions in the montmorillonite / chitosan aluminum ion polymer material; S4. Wash the sample alternately with ethanol and deionized water until the pH value is 7, and then place it in a vacuum drying oven for drying to obtain montmorillonite / chitosan aluminum ion imprinted material.

2. The method for preparing a montmorillonite / chitosan aluminum ion imprinted material according to claim 1, characterized in that: In the step S1, the purity of montmorillonite is 80% to 99%, the temperature is raised to 400 to 700°C, and the insulation time is 15 minutes to 3 hours; the acid solution is any one of sulfuric acid solution, nitric acid solution, hydrochloric acid solution, and phosphoric acid solution, the concentration is 1 to 3 mol / L, the constant temperature is 55 to 95°C, the solid-liquid ratio of thermally activated montmorillonite to the acid solution is 1:(20 to 100), and the acid dissolution time is 1 to 5 hours.

3. The method for preparing a montmorillonite / chitosan aluminum ion imprinted material according to claim 1, characterized in that: In the step S2, the mass ratio of chitosan to montmorillonite aluminum ion imprinting material is 1:2-3:1, and the mass ratio of chitosan to aluminum sulfate is 1:1-4.0:

1.

4. The method for preparing a montmorillonite / chitosan aluminum ion imprinted material according to claim 1, characterized in that: In the step S2, the temperature is heated to 110-150° C., and the heating time is 6-14 hours.

5. The method for preparing a montmorillonite / chitosan aluminum ion imprinted material according to claim 1, characterized in that: In step S3, the concentration of the sodium hydroxide solution is 0.05-0.4 mol / L, the volume is 50-250 mL, and the soaking time is 1.5-4 h.

6. The method for preparing a montmorillonite / chitosan aluminum ion imprinted material according to claim 1, characterized in that: In the step S4, the drying temperature is 60 to 90° C., and the drying time is 6 to 12 hours.

7. Use of an ion-imprinted material prepared by the method for preparing a montmorillonite / chitosan aluminum ion-imprinted material according to any one of claims 1 to 6 in selectively removing aluminum ions from a solution, characterized in that: The following steps are involved: The montmorillonite / chitosan aluminum ion imprinted material was added to a mixed solution of aluminum ions and rare earth ions whose pH value was adjusted with sulfuric acid or sodium hydroxide, and placed in a constant temperature oscillation box at 25°C for oscillation, and then filtered and separated to obtain a supernatant. The aluminum ion concentration and rare earth ion concentration in the supernatant were detected by ICP, and the removal rate and selectivity coefficient of the montmorillonite aluminum ion imprinted material for aluminum ions were calculated.

8. The use of a montmorillonite / chitosan aluminum ion imprinted material according to claim 7, characterized in that: The dosage of the montmorillonite / chitosan aluminum ion imprinting material is 3g / L to 5g / L; the pH value of the mixed solution of aluminum ions and rare earth ions is 2 to 4; and the constant temperature oscillation time is 5min to 3h.